Residual radioactivity of treated green diamonds. (August 2017) - Cassette, Philippe; Notari, Franck; Lépy, Marie-Christine; Caplan, Candice; Pierre, Sylvie; Hainschwang, Thomas; Fritsch, Emmanuel
Abstract: Treated green diamonds can show residual radioactivity, generally due to immersion in radium salts. We report various activity measurements on two radioactive diamonds. The activity was characterized by alpha and gamma ray spectrometry, and the radon emanation was measured by alpha counting of a frozen source. Even when no residual radium contamination can be identified, measurable alpha and high-energy beta emissions could be detected. The potential health impact of radioactive diamonds and their status with regard to the regulatory policy for radioactive products are discussed. Highlights: Various activity measurements on two treated radioactive diamonds are reported. Activity characterized by alpha and gamma ray spectrometry and radon emanation. Potential health impact of radioactive diamonds are discussed.